Poti in stranpoti pri diagnosticiranju primarnega aldosteronizma - Kukman, Sara (Zdravniški vestnik, 2019)
We present a patient with a tumour of the left adrenal gland who has been treated for resistant hypertension and hypokalaemia for years. Primary aldosteronism was confirmed, but despite multiple attempts at adrenal vein sampling we were unable to prove unilateral disease. Treatment with mineralocorticoid receptor antagonists was not successful, however no clear indication for surgical treatment was present. Patient's clinical and laboratory characteristics pointed to unilateral disease, so he was referred for PET CT with 11-C-metomidate in the United Kingdom. Unilateral disease was confirmed, and the patient was cured by left-sided laparoscopic adrenalectomy.
Keywords: adenom skorje nadledvičnice; adrenocortical adenoma; arterijska hipertenzija; hypertension; primarni hiperaldosteronizem; primary hyperaldosteronism